À margem da lei: a criminalização da homofobia e seus reflexos políticos e sociais - Cavalcante, Juliana Somogyi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Earlier this year, took office in Congress deputies and senators regarding the Legislature from 2015 to 2019. Most elected officials has been identified as more conservative character, which should change the work schedule in the Legislative Houses. In this context, this experimental project consists of a journalistic reporting that aims to analyze how this new composition can affect issues involving the agenda of the LGBT community, in particular, the bills criminalizing the practice of homophobia. The work aims to reach politically minded readers between 21 and 60 years, in order to educate them about the importance of this issue. Therefore, we performed the calculation of violence perpetrated against this population, studied the new profile of the Congress, analyzed how Judiciary acts front of legislative inertia and made interviews. The report compiles important data about the issue and provides, as a result, information reinforced by experts to potentially broaden the understanding of readers about the fact

No início de 2015, tomaram posse no Congresso Nacional deputados e senadores referentes à Legislatura 2015-2019. A maioria dos parlamentares eleitos foi identificada como de caráter mais conservador, o que deve mudar o esquema de trabalho nas Casas Legislativas. Neste contexto, este projeto experimental consiste em uma grande reportagem que analisa como a nova composição afeta a pauta da comunidade LGBT, em particular os projetos de leis que criminalizam a prática da homofobia. O trabalho ambiciona atingir leitores politizados, entre 21 e 60 anos, de modo a facilitar a conscientização acerca da importância desta problemática. Para tanto, foram realizados apuração do quadro de violência perpetrada contra esta parcela da população, estudo sobre o novo perfil do Congresso, análise do papel do Judiciário frente à inércia legislativa e entrevistas. A reportagem compila importantes dados acerca da questão e fornece, como resultado, informações respaldadas por especialistas, potencialmente ampliando a compreensão dos leitores a respeito do fato
Keywords: Homofobia; Projetos de lei; Poder judiciario; Homophobia